2002
DOI: 10.1046/j.1472-765x.2002.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Laccase stabilization by covalent binding immobilization on activated polyvinyl alcohol carrier

Abstract: It was possible to immobilize the laccase on carboxylated polyvinyl alcohol by activation with N-hydroxysuccinimide in HAc-NaAc buffer. The immobilized laccase is both stable and reusable. SIGNIFICANCE IMPACT OF THE STUDY: The results indicate that this immobilized laccase can be used in the removal of poisonous effluent from pulp bleaching mills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
4
23
1
Order By: Relevance
“…Upon repeated uses, either blocking of some pores of semi-IPNs by substrate or product may take place, or enzyme may lose its activity and denatures. In literature, the retained activity after 10 batch uses was reported as 60% for covalently immobilized laccase on activated poly(vinyl alcohol) (Yinghui et al, 2002). Thus the results of this study are comparable with those reported in the literature.…”
Section: Ph Temperature and Operational Stabilities Of Immobilized Lsupporting
confidence: 90%
“…Upon repeated uses, either blocking of some pores of semi-IPNs by substrate or product may take place, or enzyme may lose its activity and denatures. In literature, the retained activity after 10 batch uses was reported as 60% for covalently immobilized laccase on activated poly(vinyl alcohol) (Yinghui et al, 2002). Thus the results of this study are comparable with those reported in the literature.…”
Section: Ph Temperature and Operational Stabilities Of Immobilized Lsupporting
confidence: 90%
“…With the exception of AgRSDA-CROSS, modified RSDA exhibited lower activity at pH below pH 5.0. Similar results were observed for amylase immobilized on chitosan (Tripathi et al 2007), pectinase from A. niger immobilized on polyacrylonitrile membrane (Delcheva et al 2007), gelatin entrapped agalactosidase (Naganagouda et al 2007) and laccase immobilized by covalent binding on polyvinyl alcohol carrier (Yinghui et al 2002). The activity of PGAg-RSDA, GAg-RSDA, GlyAg-RSDA and AgRSDA-CROSS shifted towards the basic side to varying degrees.…”
Section: Immobilization On Ph Activity and Stabilitysupporting
confidence: 73%
“…However, immobilised laccase retained 65% of initial activity after 10 batches. In literature, laccase immobilised on activated poly(vinyl alcohol) retained 60% of the initial activity values after 10 cycles (Yingui et al 2002), while laccase immobilised on amineterminated magnetic nanocomposites, 80% after five consecutive operations (Xiao et al 2006). …”
Section: Reusability Of the Immobilised Laccasementioning
confidence: 99%